Creating value through development of inventory management, Case: SCA Hygiene Oy Ab - Rouru, Jutta (My University, 2015)
This research is a case study conducted for a case company in process industry. The focus of this research was to analyze company finished goods inventory levels and provide development ideas to create value through inventory management. The research is performed through the perspective of production planning function. The aim of research was to find how currect processes in inventory management can be improved to meet new company performance targets for service level, days of supply and doing so while reducing amount of capital invested in finished goods inventory. The literature review discusses inventory management and the importance of managing inventory. Different types of stock, stock models and key performance measurement are presented. Item classification is discussed in terms of categorizing product portfolio for more efficient management. Lean theory is also discussed in the development of supply chain processes. Empirical section analyzes current state of processes at case company and how it is necessary to develop processes to reach company targets. Safety stock calculations were conducted and a guideline was formed for safety stock levels. ABC-analysis helps in identifying individual impact of items in capital invested in inventory.
Keywords: inventory management; process development; optimization; working capital; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|